Prevalence of small fiber peripheral neuropathy associated with retinopathy in diabetics type 2: using biomedical test by thermographic imaging - Rodríguez-Alonso, Dante (2023)
Introduction: Small fibers diabetic peripheral neuropathy (DPN-sf) are diagnosed by biomedical vasomotor tests whose foundation is altered skin thermoregulation.Objectives: To estimate the prevalence and factors associated with DPN-sf using thermographic imaging (TI).Methods: An observational, cross-sectional, analytical study was performed in a specialized unit in the primary care setting, in which patients with type 2 diabetes mellitus were assessed by peripheral neurological tests such as tactile and vibratory sensitivity for the diagnosis of large fibers peripheral neuropathy (DPN-lf) and passive thermoregulation by TI for DPN-sf .The latter was performed on the sole using a thermographic camera in the outpatient clinic, evaluating 5 plantar thermographic measurements per subject. Then, the association between diabetics with and without DPN-sf was analyzed concerning gender, age, time of diabetic disease, type of diabetic treatment, hypertension, retinopathy, nephropathy, low carbohydrate diet, physical activity, pain symptom, and BMI. Results: 304 patients with type 2 diabetes mellitus were studied, mean age of 65.07±11.39 years, mostly male, finding DPN-lf in 14.8 %, DPN-sf in 27.3 %, and both NPD in 34.9%. The association of DPN-sf was only with the factor of the presence of retinopathy (α=0.02, C= 0.18).Conclusions: We found a high prevalence of DPN-sf using thermographic imaging that was associated with the presence of retinopathy